Retrospective Review of Magnetic Resonance Imaging of the Lumbosacral Spine: Are We Overinvestigating? - Suchit Khanduja; Vivek Loomba; Joseph Salama-Hannah; Aman Upadhyay; Neha Khanduja; Gaurav Chauhan (Neurospine, 2018)
Objective Lower back pain (LBP) is a worldwide health problem, and magnetic resonance imaging (MRI) is a common modality used to aid in its diagnosis. Although specific guidelines for assessing the necessity of MRI usage exist, the use of MRI as the initial imaging method for LBP seems to be more common than necessary in general practice. Methods We conducted a retrospective chart review of 313 patients who had undergone MRI of the lumbosacral spine during 2014–2015. We recorded and compared various factors, including age, sex, body mass index, current smoking status, race, symptoms, MRI findings, and progression to surgery within the next year. All rates were compared according to whether the MRI results showed radiographically significant findings (MRI-positive) or not (MRI-negative) using the chi-square or Fisher exact tests (if the expected cell count was <5). All analyses were performed using SAS version 9.4. Results There were no statistically significant differences in the rates of each symptom between the MRI-positive and MRI-negative groups, which accounted for 58.5% (183 of 313) and 41.5% (130 of 313) of the MRIs, respectively. The difference in the rate of surgery in the next year (18% among MRI-positive patients and 8.5% among MRI-negative patients) was found to be statistically significant (p<0.05). Conclusion Based on our findings, 41.5% of patients underwent lumbar MRI unnecessarily and 81% of patients with positive MRIs did not have surgery within the next year. Further physician training is needed to avoid unnecessary investigations and expenditures.